Alpinia officinarum Hance: a comprehensive review of traditional uses, phytochemistry, pharmacokinetic and pharmacology - Lei, Xia; Wang, Jiapeng; Zuo, Kun; Xia, Tianli; Zhang, Jinfeng; Xu, Xiangyue; Liu, Qing; Li, Xiaoliang (Frontiers in Pharmacology, 2024)
The dried root and rhizome of Alpinia officinarum Hance (A. officinarum) have been widely used in traditional Chinese medicine for thousands of years to alleviate pain, promote digestion, warm the stomach, and disperse cold. This review aims to comprehensively and in-depth summarize the most recent research on the traditional uses, phytochemistry, pharmacokinetics, and pharmacology of A. officinarum. By searching various databases including Web of Science, PubMed, Google Scholar, Elsevier, Springer, ScienceDirect, and China National Knowledge Infrastructure (CNKI) for literature on "Alpinia officinarum Hance", as well as relevant textbooks and digital documents, an overall and critical review of the subject was conducted. The traditional uses of A. officinarum were summarized, and 337 compounds from A. officinarum were summarized, including flavonoids, diarylheptanoids, volatile oils, and other compounds. Studies have found that the crude extract of A. officinarum and its compounds has a wide range of biological activities, such as improving gastrointestinal function, anti-inflammatory properties, anti-tumor activity, antibacterial properties, memory enhancement, and analgesic effects. Modern pharmacological studies have provided strong evidence and explanations for the traditional medicinal uses of A. officinarum, which brings a broad prospect for its medicinal use. However, more research is needed to explore the structure-activity relationship and potential mechanisms of action of its bioactive chemicals. Furthermore, it is essential to conduct more clinical trials in order to accelerate research and 2 development of the drug.